The effect of gestured instruction on the learning of physical causality problems. - Carlson, Crystal; Jacobs, Steven A.; Perry, Michelle; Church, Ruth Breckinridge (Gesture, 2014)
Recent research has demonstrated instruction that includes gesture can greatly impact the learning of certain mathematics tasks for children and much of this work relies on face-to-face instruction. We extend the work on this problem by asking how gesture in instruction impacts adult learning from a video production for a science concept. Borrowing from research by Perry and Elder (1997), the research presented here examines what role adding gesture to instruction plays for adults learning about gear movement. In this pretest-instruction-post-test design, 56 college-aged participants were asked to complete problems relating to gear movement. Participants viewed either an instructional video in which an instructor used speech only (control) or speech-plus-gesture (experimental) to explain a fundamental principle in the physics of gear movement. Results showed that adults who knew less actually learned more and that instruction was effective, but significantly more effective when gesture was added. These findings shed light on the role of gesture input in adult learning and carry implications for how gesture may be utilized in asynchronous instruction with adults.